Determinants of Malnutrition in Children Under Five at Effutu Municipality - Tackie, V. (University of Ghana, 2017)
Background: Malnutrition is an underlying factor in many diseases for both children and adults and is particularly prevalent in developing countries, where it affects one out of every three preschool-age children. Under nutrition (malnourished) a form of malnutrition has been a worldwide problem which is being tackled in various ways and is usually prevalent among children in developing economies. One of the appropriate measures to support the fight against malnutrition in general and undernutrition specifically is to know the nutritional status and conditions of the population so that appropriate measures can be taken to address them. Objective- The study sought to find out the proportion of children under five years who were malnourished and examined what socio-economic, household practices, child health care seeking practices and cultural beliefs and practices are associated with the most prevalent form of undernutrition Methodology: A community based research was conducted to assess the nutritional status of children under five years in Effutu municipality for a total of 350 children. With the use of a structured questionnaire, data on children and care givers was collected. Data was entered into Microsoft Excel 2010. WHO Anthro software version 3.2.2.1 was used in determining the z-scores and SPSS software version 20 was used to perform univariate, bivariate and logistic regression analysis. A P<0.05 was deemed statistically significant. Results-Out of the 350 children under five, the most prevalent undernutrition case is stunting (59%) and the least malnutrition case was wasting (19%). Stunting was most prevalent among children in the age group of 12-23 months (35.5%). Occupation of Mother and Household income were socio-economic factors that were found to be significantly associated with stunting at 95% significant level. What is done when the child is sick was the only child health care seeking factor associated with stunting at 95% significant level. The number of times child feeds daily is the only-household practice that is associated with stunting at 5% significant level. None of the cultural practices and believe system had any significant association with stunting. With regards to the socioeconomic factors, Children whose parents who are self-employed are about twice likely to be stunted than those who are unemployed (OR=2.18; 95% CI, 1.14 - 3.246). Those who earn more than Ghc1000 are about two and halftimes more likely to be stunted than those who earn less than Ghc100 (OR=2.672; 95% CI, 2.198 - 47.145). Those who consult traditionalist when their child is sick are less likely to stunted than those who visit the hospital when the child is sick by a multiplicative factor of 0.355 (OR= 0.355; 95% cr, 0.098 - 0.612). Conclusion- The study showed that of the economic factors, mother's occupation and household income was significantly associated with their child being stunted. The findings of the study also showed of the house hold practices, the number of times a child feeds in a day was significantly associated with their child being stunted. Child health care practices and stunting, also showed no significant relationship. Which was not the same as in the case of cultural beliefs and practices and stunting among children under five years.
MPH
Keywords: Malnutrition; Children Under Five; Effutu Municipality; Ghana